2022
DOI: 10.1021/acsestengg.1c00344
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Cyanobacterial Harmful Algal Blooms (cHABs) and Cyanotoxins by Electrochemical Oxidation: From a Bench-Scale Study to Field Application

Abstract: Cyanobacterial harmful algal blooms (cHABs) and the concurrent release of cyanotoxins have become an emerging threat to aquatic life and drinking water safety. It is challenging for conventional water treatment infrastructures to mitigate cHAB events that occur frequently and irregularly. This study developed an emergency-responsive electrochemical oxidation and filtration (EOF) process that enables the pump-and-treat of phytoplankton plumes and cyanotoxins. Fundamental studies indicate that the EOF process ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…We advanced the EO process by developing Ti 4 O 7 filter anodes with pore sizes of 24−53 μm for the treatment of HABimpacted lake water at both lab and full scales. 15 Similar to other reported anode materials, the Ti 4 O 7 filter anodes oxidize chloride in lake water to chlorine to inactivate algae cells and oxidize cyanotoxins. The flow-through operation (by pumping water out of the filter anodes immersed in the plume) significantly promoted convective mass transfer and thereby achieved higher treatment performance than homogenous chlorination.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…We advanced the EO process by developing Ti 4 O 7 filter anodes with pore sizes of 24−53 μm for the treatment of HABimpacted lake water at both lab and full scales. 15 Similar to other reported anode materials, the Ti 4 O 7 filter anodes oxidize chloride in lake water to chlorine to inactivate algae cells and oxidize cyanotoxins. The flow-through operation (by pumping water out of the filter anodes immersed in the plume) significantly promoted convective mass transfer and thereby achieved higher treatment performance than homogenous chlorination.…”
Section: Introductionsupporting
confidence: 71%
“…and Microcystis aeruginosa (UTEX Culture Collection of Algae), were incubated in a shaker incubator (Innova S44i, Eppendorf) with 10-30% photosynthetic light following our previous study. 15 The bench-scale tests involved mesh-type (0.5 × 0.8 mm rhombus openings) anode with either NATO or antimony tin oxide (ATO: Sb-SnO 2 ) coatings. The NATO and ATO anodes were prepared by dip-coating titanium mesh into sol-gel solutions of metal-citrate complexes, followed by calcination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work identified theoretically and experimentally that a REM might feature nonuniform oxidation activity along its reaction depth (about hundreds of micrometers). 149 The region where • OH is generated was found to be located just a few μm beneath the EAM surface (less than 1% of the reaction depth), attributed to the rapid potential drop in the EAM, and the nonuniform reactive character might render the REM of a strong direct electron transfer ability, enabling the rapid removal of electron-rich micropollutants even at low potentials (Figure 10). However, unsatisfactory removal of electron-poor micropollutants has been observed, and a higher potential was required to prompt the generation of • OH.…”
Section: Scaling-up Challengesmentioning
confidence: 99%
“…Feng et al (Feng et al, 2022) used an ultrasonic cavitation process to remove Microcystis aeruginosa. Yang et al (Yang et al, 2022) developed an electrochemical degradation process to remove cyanotoxins released from the cyanobacterial harmful algal blooms. Zheng et al (Zheng et al, 2022) reported that 90 % of Microcystis aeruginosa was removed using a sulfate radical-based process.…”
Section: Introductionmentioning
confidence: 99%